Koli women in front of Hingla Devi Temple - Mumbai Archive Project Team (Jio Institute, 2024)
Koli women assemble in front of Sri Hingla Devi temple in Versova village. Hingla Devi (also known as Hingula) is venerated as a Kuladevata among the Koli community. A Kuladevata is the family deity or patron deity of a particular clan or family.